Application Of The Silver Meal Heuristic Method For Optimizing Tempe Raw Material Inventory Costs On The Web Aplication - Mohamad Isro' Eddy; Rahmat Deddy Rianto Dako; Idham Halid Lahay; Wahab Musa; Ifan Wiranto; Amirudin Yunus Dako (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2026)
The tempeh industry requires an accurate raw material inventory management system to reduce costs and maintain production continuity. At the HB Azaki Tempeh Home Industry, stock management is still carried out conventionally, which often results in inaccuracies in determining the quantity and timing of orders. This study aims to develop a web inventory planning application that implements the Silver Meal heuristic method to calculate the optimal order quantity based on actual demand data. The application development follows the Rapid Application Development (RAD) method and system testing is carried out using black box testing. The results show that the Silver Meal method is able to reduce total inventory costs from Rp6,480,000 to Rp5,690,404, or an efficiency of 12.23% with a decrease in ordering frequency from 18 to 9 times. The scientific contribution of this study lies in the integration of the Silver Meal method into a web application that allows calculations to be carried out automatically, quickly, and with minimal manual errors. This research provides practical benefits for the small-scale tempeh industry as a reference in making more efficient and measurable raw material ordering decisions.